OFFENSIVE AND DEFENSIVE CAPABILITY COMPARISION BETWEEN IVER HUITFELDT CLASS AND PKR105 CLASS BASED ON SALVO MODEL - Avando Bastari; Ekaris Kusuma; Okol Sri Suharyo; Priyadi Hartoko (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Warship ability owned by Indonesian Navy is expected to have deterrence effect on other countries that want to disturb the sovereignty of Indonesia. Therefore, the right decision is needed to determine which warship should be chosen to carry out the task of guarding Indonesia's territorial waters. The newest warship that has a deterrence effect and is owned by the Indonesian Navy is the KRI PKR105 class. This ship has reliable capabilities both in terms of offensive and defensive because it is equipped with qualified equipment and weapons. Meanwhile, in future plans, the Indonesian Navy is interested in having a Danish-made Iver Huitfeldt class warship which also has a fairly reliable capability. In this paper, we will discuss the calculation of the capabilities of the PKR105 class and Iver Huitfeldt class which are planned to be purchased by the Indonesian Navy based on the Salvo Model. From the calculation, it can be seen that PKR105 class has the same offensive capability as Iver Huitfeldt class but Iver Huitfeldt class has higher defensive caspability than PKR105. This is because the tonnage of Iver Huitfeldt class is greater than PKR105 as one of the staying power parameters for calculating defensive ability. To overcome the shortage of PKR105 defensive capabilities, a 21 million CIWS can be added as one of the defensive power parameters in calculating defensive capability considering that there is still a difference in the PKR105 price of 285 million with the Iver Huitfeldt class price of 325. With this upgrade option then it can be used as one of the considerations in determining the type of ship that can be selected to increase the combat capability of the fleet. Keywords : Iver Huitfeldt Class , PKR105 class, reserve fuel, Salvo Model.